Exploring how blockchain transparency and bullion business synergy foster trust in Islamic gold tokenization among digitally literate urban Muslims in Indonesia - Sumar'in; Mokmin Basri (Economic Military and Geographically Business Review, 2026)
Background: Background: The rapid development of blockchain technology has encouraged the emergence of Islamic gold tokenization as an innovative Sharia-compliant digital financial instrument. However, public trust in blockchain-based Islamic financial products remains a critical challenge, particularly among urban Muslim investors in emerging markets such as Indonesia. Methods: This study investigates the effects of blockchain transparency and bullion business synergy on trust in Islamic gold tokenization, with digital literacy acting as a moderating variable. The research adopts a quantitative explanatory design grounded in the Technology Acceptance Model (TAM) and Trust-Based Adoption Theory. Data were collected through online surveys from 376 urban Muslim respondents in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The results demonstrate that blockchain transparency, bullion business legitimacy, and digital literacy each have positive and significant effects on trust in Islamic gold tokenization. In addition, digital literacy significantly strengthens the relationships between blockchain transparency and trust, as well as between bullion business legitimacy and trust. These findings indicate that digitally literate investors tend to place greater trust in blockchain-based Islamic financial products supported by tangible gold assets. Conclusion: The study concludes that trust in Islamic gold tokenization is shaped not only by technological transparency and asset-backed legitimacy but also by the level of users’ digital literacy. Strengthening digital literacy can therefore enhance public confidence in Sharia-compliant fintech ecosystems. Novelty/Originality of this article: This study contributes to the Islamic fintech literature by empirically examining digital literacy as a moderating variable in the relationship between blockchain transparency, bullion business legitimacy, and trust in Islamic gold tokenization. The study also provides a contextual contribution by focusing on urban Muslim investors in Indonesia and the integration of blockchain transparency with bullion-backed Islamic digital finance.